A green route of antibacterial films production from shrimp (Penaeus monodon) shell waste biomass derived chitosan: Physicochemical, thermomechanical, morphological and antimicrobial activity analysis - Md. Mahmudur Rahman; Mohd. Maniruzzaman; Ripon Kumar Saha (South African Journal of Chemical Engineering)
As a result of the excessive dependency on synthetic polymer/plastic products, both industries and mankind have been generating a huge amount of hazardous plastic waste. That could be recognized as a breakneck tread on for total environment due to their nonbiodegradable nature. Thus, to solve this problem replacement of the hazardous synthetic fossil-based plastic with biopolymeric materials is very crucial. But, due to the deficiency of the most critical understanding, designing of the biopolymeric materials from natural resources have signified a big challenge. However, researchers are trying to develop a suitable route to solve this issue. By this study a green route of production of antibacterial films from the agro-waste biomass has been developed. Whereas the highly active chitosan were extracted from shrimp (Penaeus monodon) shells by conducting demineralization, de-proteinization, and deacetylation reaction. The chitosan-acetate films were fabricated by using the EIPS operation to enhance their overall properties. The samples were characterized by SEM, ATR-FTIR, 13C CPMAS NMR, TGA, TS, biodegradability, and antimicrobial activity exploration. The results advised that the newly fabricated biofilms are highly thermally stable, possessed several active binding sites with a uniform nonporous solid microstructure. Also exhibited a higher mechanical tensile strength (nearly 120.27 ± 0.091 N/mm2), elongation properties (around 43.98 ± 0.098 %), and a high antimicrobial activity. While the maximum zone of inhibition and MIC value were found around 45 mm and 5 µg for Staphylococcus aureus. Due to these outstanding properties, this biofilm would be beneficially used in several engineering, industrial, and bio-medical sectors for the green environmental protection.